Pemanfaatan Sarana Dan Prasarana Untuk Meningkatkan Mutu Sekolah - Pitaloka, Adelia Eka (Pedagogi: Jurnal Pendidikan Dasar, 2023)
One of the vital components in the learning process in schools is facilities and infrastructure. The creation of quality and high-quality education cannot be separated from various things, one of which is the optimal utilization and management of facilities and infrastructure. The problem found in this study is the lack of utilization of facilities and infrastructure from schools so that the quality of education is low. The purpose of this research is to find out an application that can be made so that school quality can be achieved properly through school facilities and infrastructure. The method used in this study is the Systematic Literature Review (SLR) approach with reference to literature sourced from articles in national journals published from 2015 to 2022 excluding from books, newspapers, or the results of conference proceedings. The research results obtained are in the use of infrastructure so that school quality can improve through the application of several principles, namely the principle of achieving goals, the principle of efficiency, the principle of clarity of responsibility, and the principle of cohesiveness.